Pengembangan Lembar Kerja Peserta Didik Mata Pelajaran Informatika Pada Tingkat SMA - Muhammad Hidayat Lammi; Westy Tenriawi; Ary Herlina Kurniati H.M; Hermila .A (CV. Eureka Murakabi Abadi, 2025)
The background of this research is based on the need for contextual, interactive teaching materials that are in line with the characteristics of the curriculum and the needs of students in developing 21st century skills. The research method used is development with an instructional design approach, which includes the stages of planning, design, expert validation, and revision. The LKPD product was developed with reference to the learning outcomes of the Merdeka Curriculum and designed to support computational thinking, digital literacy, and problem-solving skills. The validation process was carried out by two expert validators, covering the aspects of construction, technical, and content. The validation results showed that the LKPD product obtained a high average score, with a “Valid” category in all aspects of the assessment. The construction aspect scored an average of 4.6; the technical aspect scored 4.7; and the content aspect scored 4.9. These findings indicate that the developed Informatics LKPD is suitable for use as supporting teaching materials in the learning process. Revisions were also made based on validator feedback, particularly regarding the alignment of learning indicators with the content and time allocation. In conclusion, the developed LKPD has good content, appearance, and structure so that it can be used in teaching and learning activities. This study is expected to contribute to the provision of effective and relevant teaching media in the current digital era.